Web-Based Periodic Salary Increase Information System at The Biddokkes Polda Jambi Using Waterfall Method - Sugeng Wibowo; Mutmainnah (Information Technology and Science (ITScience), 2026)
The administrative process for periodic salary increases for personnel at the Biddokkes Polda Jambi currently faces efficiency challenges, including the risk of data entry errors and delays in monitoring the salary increase periods. This study aims to develop a web-based periodic salary increase information system capable of automating data collection and providing timely notifications. The system development method used is the Waterfall model, which includes the stages of requirements analysis, design, coding, testing, and maintenance. The results of the study indicate that the developed system successfully minimizes data input errors and accelerates the administrative verification process compared to manual methods. Through functional testing using the Black Box Testing techniques and User Acceptance Test (UAT) evaluation, all major system features were proven to function with a 100% success rate and were well-received by users, as evidenced by a system acceptance rate of 90%. With this system in place, human resource management at the Biddokkes Polda Jambi become more measurable, transparent, and effective in supporting personnel administration processes.